Are there any long‐term detrimental effects from soy formula?. Issue 3 (March 2015) - McKenzie, Mary L.; Haynes, James W.
Abstract : Evidence‐Based Answer : Soy formula feeding has no effect on growth (SOR: A, systematic review of RCTs and cohort studies with consistent results). Soy formula has been associated with extremely premature thelarche (prior to age 2) and increased duration and discomfort of menses in adulthood (SOR: C, case‐control and cohort studies with multiple comparisons). But the American Academy of Pediatrics states that there is no convincing evidence that soy formulas affect human development, reproduction, or endocrine function (SOR: C, expert opinion).